2021
DOI: 10.1007/s12020-021-02758-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Sars-COV-2-related thyrotoxicosis in survivors of Covid-19: a prospective study

Abstract: Purpose To evaluate the post-coronavirus disease-19 (COVID-19) outcome of thyroid function in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-related thyrotoxicosis. Methods This was a single-center prospective study involving 29 patients (11 females, 18 males; median age 64 years, range: 43-85) with thyrotoxicosis diagnosed after hospitalization for COVID-19 and then followed-up for a median period of 90 days (range: 30-120) after hospital discharge. At follow-up, patients were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
5
14
1
Order By: Relevance
“…These studies are poorly comparable, due to the different thresholds applied to identify low T subjects and the heterogeneity of the populations involved (e.g., ICU vs asymptomatic subjects). The high prevalence observed in our cohort suggests a specific association between SARS-CoV-2 infection and gonadal failure, possibly involving the whole hypothalamic-pituitary–gonadal (HPG) axis, in association with a higher degree of systemic inflammation, as similarly described for other endocrine glands [ 28 , 42 ].…”
Section: Discussionsupporting
confidence: 53%
“…These studies are poorly comparable, due to the different thresholds applied to identify low T subjects and the heterogeneity of the populations involved (e.g., ICU vs asymptomatic subjects). The high prevalence observed in our cohort suggests a specific association between SARS-CoV-2 infection and gonadal failure, possibly involving the whole hypothalamic-pituitary–gonadal (HPG) axis, in association with a higher degree of systemic inflammation, as similarly described for other endocrine glands [ 28 , 42 ].…”
Section: Discussionsupporting
confidence: 53%
“…Pizzocaro et al recruited 58 patients with COVID-19 associated thyrotoxicosis where 23 (39.7%) of the patients died. Among the rest of the patients, 29 patients were enrolled to the prospective study [18]. The authors reported that all but one subject with COVID-19 related thyrotoxicosis became euthyroid after a median of 90 days while one-third of the patients revealed hypoechogenicity on ultrasound evaluation associated with higher TSH values at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this rate is also similar to the background rate of abnormal thyroid ultrasonographic echogenicity reported in population studies (around 10%) [ 31 ]. Existing studies have focused on the ultrasonographic features of COVID-19 survivors who had symptomatic SARS-CoV-2-related thyroiditis in acute illness [ 7 ]. In contrast, our study attempted to identify any subclinical ultrasonographic suggestion of thyroid parenchymal damage, as these abnormalities could predict subsequent thyroid dysfunction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, thyroid USG has been mainly performed in patients who had clinically overt thyroid dysfunction in acute COVID-19 [ 6 , 7 ]. Little is known in a broader sense on how the infection may affect the subsequent ultrasonographic features and thyroid volumes for COVID-19 survivors.…”
Section: Introductionmentioning
confidence: 99%